PENGARUH INCOME SMOOTHING TERHADAP EARNING RESPONSE PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI - Alwiyah Alwiyah; Charis Sholihin (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2015)
The value in the financial statements as net profit the company is regarded as a signal that indicates the value of the company. It makes the investor attention centered on profits of a company. Investors often focus only on the profit information, regardless of the procedures used to generate the earnings information. As such, the company does not cover possible will do the alignment.This research was conducted to find out the influence of Income Smoothing toward Earning Response on manufacturing companies listed on the Indonesia stock exchange. To know the management actions influence profit Income Smoothing through financial reporting information to a market reaction if a financial report containing the information. The samples on this research there are manufacturing companies listed on the Indonesia stock exchange during the period 2010-2014. Data collected through purposive sampling method in manufacturing company that detected doing Income Smoothing. Analysis of linear regression used is simple. Through simple regression analysis note that the variable income Smoothing is not significantly to influential variables Earning Response. This is demonstrated by the results of the regression i.e. the value significance of 0.137 greater than (α) 0.10. Rated R and square are very low i.e. 0.141.Keywords: perataan laba (Income Smoothing), reaksi pasar (Earning Responce)